Development of socioeconomic indicators for measuring the population wellbeing in lembah klang-Langat extended metropolitan region, Malaysia - Yazid Saleh (Tanjung Malim, 2021)
Development of socioeconomic indicators for measuring the population wellbeing in lembah klang-Langat extended metropolitan region, Malaysia by Yazid Saleh